Yield of chicory ‘Folha larga’ and ‘Pão de açúcar’ according to planting density - Candian, Joara Secchi; Redígolo, Mateus Vinicius Narciso; Antunes, Walter Luiz de Proença; Cardoso, Antonio Ismael Inácio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 322-328) : ilustraciones color.